(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
When local residents make and broadcast their own programming and help run the station, it is referred to as community radio. It is a gathering and collaboration space for the community. It’s a lot of fun, and it’s often life-changing. Individual creativity and self-empowerment are common outcomes. Participants find it extremely rewarding not just to make radio in this unique way, but also to contribute to the transformation of community life.There are 338operational community radio stations in India till April , 2022. The Community Radio can help us in addressing social, economic, cultural, educational, health, water and sanitation and disaster related issues more effectively and strategically. In order to highlight the importanceand effectiveness of community radio for the community development of , this study has been conducted based on the secondary data. The study’s goal is to learn more about the value of community FM radio inIndia , particularly in backward Marginalized areas.